Analisis Penerimaan PAD Pada Dinas Perikanan dan Peternakan Kabupaten Tebo - Eko Purnarianto (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2016)
Abstract. This study aims to analyze potential, efficiency, effectivity and contribution of PAD admission at Department of Fishery and Animal Husbandry in Tebo Regencyincluding the strategy establishment to increase its revenue.The analysis used is a potential formula, efficiency ratio, effectivity ratio, contributions ratio and SWOT analysis.The results shows that the potential revenue of retribution slaughterhouse (RPH), the potential sales of livestock, and potential sales fishery product are beyond the current target. The efficiency level of retribution slaughterhouse (RPH) and sales of fishery product is poor, but the sales of livestock is very efficient. Effectivity level of livestock and fishery product sales are low, whileretribution slaughterhouses(RPH) is not effective regarded to its potential  but in the contrary for its target. Contribution of PAD admission of Fishery and Animal Husbandry Department is very low regarded Tebo Regency PAD. The result of SWOT analysis of retribution slaughter house (RPH) admission using WO (Weakness-Opportunity) strategy, livestock sales using SO (Strength-Oppurtunity) strategy, and fishery product sales using ST (strength-threat) strategy. Keywords: Retribution SlaughterHouse (RPH), Sales of Fishery, Livestock Sales, SWOT Analysis   Abstrak. Penelitian ini bertujuan untuk menganalisis potensi, efisiensi, efektivitas dan kontribusi penerimaan PAD pada Dinas Perikanan dan Peternakan Kabupaten Teboserta menetapkan strategi untuk peningkatan penerimaan PAD. Analisis yang digunakan adalah rumus potensi, rasio efisiensi, rasio efektivitas, rasio kontribusi dan analisis SWOT.Hasil penelitian menunjukkan bahwa potensi penerimaan retribusi rumah potong hewan (RPH), potensi penjualan hasil peternakan, potensi  penjualan hasil perikanan lebih besar dari target yang telah ditetapkan. Tingkat efisiensi retribusi RPH dan penjualan hasil perikanan tidak efisien, penjualan hasil peternakan sangat efisien. Tingkat efektivitas penjualan hasil peternakandan penjualan hasil perikanan tidak efektif, retribusi RPH tidak efektif berdasarkan potensi dan sangat efektif berdasarkan target.Kontribusi penerimaan PADDinas Perikanan dan Peternakan sangat kurang terhadap PAD Kabupaten Tebo. Hasil analisis SWOT penerimaan retribusi RPH menggunakan strategi WO (Weakness-Opportunity), penjualan hasil Peternakan menggunakan strategi SO (Strength-Oppurtunity), dan penjualan hasil perikanan menggunakan strategi ST (Strength-Threat). Kata Kunci : Retribusi Rumah Potong Hewan, Penjualan Hasil Perikanan, Penjualan Hasil Peternakan, Analisis SWOT